Fragility of the Future: Phenomenology of the Old-age - Venebra, Marcela (2021)
The central thesis of this paper is that old-age is not confused with illness, and its distinction is rooted in the temporal dimension of the living body. The body’s time is an ingredient of the self-consciousness (selfconstitutive) in the horizon of the possibilities and potentialities of the ego, which in old-age appear under a fragile and worn condition. I present this thesis in three main parts: first, I try to distinguish the dimensions of time of nature and subjective time. In these distinctions old age is clarified, with respect to the time of nature, as the phase of normal fulfillment or of the broadest and unitary development of the body as a living thing. In the second part I define the fragility of the future as the structural specificity of the time horizon of old-age. Finally, in the third part I explore how this temporal condition determines the self-consciousness (self-constitution) and the signification (historization) of its own body in old-age. The methodological frame of this investigation is taken from the Husserlian analysis of constitution in Ideas II.